Uso de símbolos ancestrales indígenas en la producción de contenidos persuasivos: análisis del caso Yololo - Vernimmen Aguirre, Guadalupe María (2019)
The article studies the case of the Yololo Cultural Center, a place that specializes in the recovery and interaction of indigenous ancestral and traditional knowledge from spirituality. In this sense, the dynamic analysis of the analog and digital communication of the place stands out, as well as the use of atavistic symbols that contribute to the contents, how and in what way they are understood, taking into account the spaces of interaction and intercultural dialogue. From an interdisciplinary perspective and through the results of an ethnomethodology corresponding to an exploratory investigation, the meanings that grant social validity to spirituality and health practices for the creation, re-invention and negotiation of social identities are studied.